Análise de imagens para a determinação de parâmetros de cinética química - Oliveira, Isabella Moura e (2024)
A low-cost experimental apparatus was built from a video capture device (smartphone) and a lighting box. This system was used to determine the rate constant of fading of Phenolphthalein in NaOH (pH > 10) using video analysis. All computational development was carried out using free software. The analytical methodology developed is statistically equivalent to the determination made by the reference spectrophotometric method (λ = 550 nm). A case study using categorization was designed to evaluate the use of video analysis methodology as a teaching tool in a class on the Experimental Physical Chemistry course. The results obtained reinforce that the methodology developed showed good agreement between the results obtained in the classroom and those in the literature. There was also a positive interest among students in the alternative approach, highlighting the practicality and mobility offered by the new methodology. In other words, this methodology can also be effective in teaching laboratories, especially as a low-cost alternative to the use of UV/Vis spectrophotometers.